2021
DOI: 10.1038/s41430-021-00875-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oat β-glucan on postprandial blood glucose and insulin responses: a systematic review and meta-analysis

Abstract: To determine the effect of oat β‑glucan (OBG) on acute glucose and insulin responses and identify significant effect modifiers we searched the MEDLINE, EMBASE, and Cochrane databases through October 27, 2020 for acute, crossover, controlled feeding trials investigating the effect of adding OBG (concentrate or oat-bran) to carbohydrate-containing test-meals compared to comparable or different carbohydrate-matched control-meals in humans regardless of health status. The primary outcome was glucose incremental ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 95 publications
1
38
0
6
Order By: Relevance
“…11,33 On the other hand, low molecular weight BG has advantages such as not causing undesirable sensory properties, slowing filtration of solutions, or precipitation, thus extending its applications in the food and pharmaceutical industries. 34 However, some studies have shown that modifying BG's molecular weight reduced its anti-hypercholesterolemic properties, 35 reducing its efficacy in lowering LDL-C concentrations, 36 glycaemic and insulinemic responses, 37 and body weight. 38 In contrast, consuming high or low molecular weight BG did not lead to differences in blood lipids, insulin or glucose levels in another human study, 39 thus the interest of studying the two BG products used in the present intervention trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,33 On the other hand, low molecular weight BG has advantages such as not causing undesirable sensory properties, slowing filtration of solutions, or precipitation, thus extending its applications in the food and pharmaceutical industries. 34 However, some studies have shown that modifying BG's molecular weight reduced its anti-hypercholesterolemic properties, 35 reducing its efficacy in lowering LDL-C concentrations, 36 glycaemic and insulinemic responses, 37 and body weight. 38 In contrast, consuming high or low molecular weight BG did not lead to differences in blood lipids, insulin or glucose levels in another human study, 39 thus the interest of studying the two BG products used in the present intervention trial.…”
Section: Discussionmentioning
confidence: 99%
“…Open response relationship between barley BG intake and its cholesterol lowering effect. 41 In turn, in the meta-analysis just published by Zurbau et al, 37 the magnitude of glucose reduction by oat BG depended on the dose, along with the molecular weight.…”
Section: Food and Function Accepted Manuscriptmentioning
confidence: 96%
“…In einer Metaanalyse von 103 Vergleichsstudien mit 538 Studienteilnehmern war der Zusatz von Hafer-β-Glucan zu kohlenhydrathaltigen Mahlzeiten nachweislich mit einer reduzierten Glukose-und Insulinantwort assoziiert [389].…”
Section: Kommentarunclassified
“…Oats are a whole grain containing the soluble dietary fiber β-glucan [ 2 ]. Oat β-glucan (OBG) reduces serum LDL-cholesterol [ 3 , 4 ] and postprandial glycemic responses [ 5 ], physiological effects associated with reduced risk for cardiovascular disease [ 6 ] and type 2 diabetes [ 7 ], respectively. Dietary fibers such as OBG are not absorbed in the small intestine and reach the colon where they increase the mass of the colonic contents and may be partly or completely fermented by colonic microbiota, effects which have desirable and undesirable consequences as explained below.…”
Section: Introductionmentioning
confidence: 99%